Solving the identity of Odynerus spiricornis Spinola, with notes on the South European species of Paragymnomerus Blüthgen (Hymenoptera, Vespidae, Eumeninae) - Selis, Marco (Zootaxa, 2025)
The identity of Odynerus spiricornis Spinola, 1808 is discussed, revealing a long history of misinterpretations surrounding this name and some of the other taxa included in the genus Paragymnomerus Blüthgen, 1938. Three species of Paragymnomerus are recognized in southern Europe: P. discoidalis (de Saussure, 1856), sp. resurr. et comb. nov. (= P. spiricornis auct.), P. dusmeti Blüthgen, 1962, and P. spiricornis (Spinola, 1808) (= P. amitinorum Blüthgen, 1952, syn. nov.). The subspecies P. spiricornis turanicus (Kostylev, 1940) is raised to species-level (P. turanicus stat. nov.). The name Odynerus rugulosus Rudow, 1876 is designated as a nomen dubium. An illustrated key for the identification of the South European species of Paragymnomerus is provided. Lectotypes are designated for Odynerus discoidalis de Saussure, 1856 and Odynerus spiricornis var. iberica Dusmet, 1909.